Sustainable Foreign Economic Activity of Gas Industry Enterprises: Trends, Tactics and Strategy - IMANGOZHINA, Zinat; DOSKALIYEVA, Bayan (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).22, 2019)
Sustainable foreign economic activity of gas industry enterprises was done in frames of project management approach in energy company (the case of JSC "Samruk-Energo"). We have considered from the perspective of development of the area of a region where projects are being implemented in the energy sector in this region, as in the analysis and subsequent evaluation of projects is difficult to identify purely economic component of the project to assess the effectiveness of the project and management. In our view, this should be approached from the perspective of sustainable development, not only the company but also the region. Especially, it is necessary to take into account the company's development strategy, which positions itself as a company that creates value for shareholders, employees and society as a guarantor of Kazakhstan's high-tech energy and supplier of Eurasia, guided by the principles of the care of the environment and lean manufacturing